Hubungan Penggunaan Helm dengan Derajat Cedera Kepala Akibat Kecelakaan Lalu Lintas pada Pengendara Sepeda Motor di RSUP Dr. M. Djamil Padang Tahun 2016-2017 - Sharon Serafim Bosawer; Rizki Rahmadian; Zelly Dia Rofinda (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Traffic accidents are a public health problem in the world, and the main cause of head injury cases with the main contributor is motorcycle riders. The use of helmets on motorcycle riders can reduce the risk of head injury, by reducing the impact force on the head. Objective. The objective of this study is to determine the relationship between the use of helmet and the degree of head injury due to a traffic accidents on motorcyclists at RSUP Dr. M. Djamil Padang in 2016-2017. Methods. This study was an analytic study with cross sectional design.The sample was conducted by probability sampling technique using random sampling with 93 samples. Data were obtained from medical records of head injury patients who suffered traffic accidents using motorcycle and treated at RSUP Dr. M. Djamil Padang in 2016-2017. Data were analyzed using chi square test. Results. The results showed man (67,7%), did not use helmet (72%), and most types of head injuries are severe head injuries (50,5%. There was a significant relationship between the use of helmets with the degree of head injury due to traffic accidents on motorcycle riders (p=0,002). Conclusion. There was a relationship between the use of helmets on motorcycle riders with the degree of head injury due to traffic accidents. Keyword : Traffic acidents, head injury, helmet